Pendidikan Karakter Agama Islam pada Siswa MTs Miftahul Ulum Purwakarta Jawa Barat - Deden Kurnia Adam; Aan Hasanah; Arifin, Bambang Samsul; Nurhakim, Aam; Hadiansyah (CV Putra Publisher, 2024)
Islamic religious character education has an important role in forming students' personalities who have noble, honest and responsible character. This research aims to analyze the implementation of Islamic religious character education for students at MTs Miftahul Ulum Purwakarta, West Java. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Primary data sources are students, teachers and school principals. Secondary data sources include books and relevant journals. The research results show that Islamic religious character education at MTs Miftahul Ulum is carried out through various activities, such as routine recitations, congregational prayers, Al-Qur'an learning, as well as religious extracurricular activities. Factors supporting the success of character education include teacher involvement, parental support, and a conducive school environment. However, there are several obstacles such as limited time and facilities. In conclusion, Islamic religious character education at MTs Miftahul Ulum has been going well, but further efforts are needed to overcome existing obstacles so that the goals of character education can be achieved optimally.